The oral health of patients with burning mouth syndrome (Эндодонтия Today)
It is necessary to study the clinical dental status of patients with burning mouth syndrome. This study showed high prevalence of caries and dystrophic diseases of periodontal patients with burning mouth syndrome. Burning mouth syndrome and substantiates the necessity of carrying out the complex of measures aimed at reducing the intensity of caries and periodontal diseases. When planning treatment, it is necessary to refer patients to a neuropsychiatrist to assign adequate provided psychotropic treatment, as well as other specialists of the corresponding profile for the treatment of chronic somatic diseases.